Intrauterine Contraceptive Devices Choice among Women of Reproductive Age and Its Contributing Factors - Imas Rafiyah (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Intrauterine contraceptive devices (IUDs) is a safe and effective method of long-term contraception. However, many women in reproductive age do not intend to use this contraceptive especially in rural areas. So, the purpose of this study was to identify factors that contribute on women of reproductive age in choosing intrauterine contraceptive devices including intentions, information, personal autonomy, social support, and situation. Research method used quantitative descriptive. The population was the entire women in reproductive age who were 30 years age or older, had 2 or more children and they were alive. The number population was 210 people. The sample of these was 66 women recruited by a simple random sampling technique. The data were collected through questionnaire developed researcher based on Snehandu’s theory. Then the data were analized using percentage. The results showed that of 66 respondents, 80.3% did not intended using intrauterine contraceptive devices because most of them were fear for its side effect (41.5%). The number of respondents who less information about it were 66.7%, it was especially in term of side effects (74.2%). Unsupported situation in choosing this contraceptive method was value “more children more sustenance” (65.2%). In addition, 84.9% respondents were lack of social support though 97% respondens had personal autonomy in determining contraceptive methods. To conclude that most of women of reproductive age in Margaluyu village had no intention using intrauterine contraceptive devices. Around half of them were fear for side effects, lack of information, their belief, lack of social support. Almost of them had autonomy in choosing contraceptive method. Thus nurses needed to provide health education about intrauterine contraceptive devices by emphazing on the side effect and benefit of this not only for women bat also for husbands and community.